Comparison of hemodynamic, biochemical and hematological parameters of healthy pregnant women in the third trimester of pregnancy and the active labor phase - Flisser Ana; Reyes-Paredes Norberto; Villanueva-Egan Luis; Kawa-Karasik Simón; Martínez-Ocaña Joel; Rodríguez-Dennen Fernando; Olivo-Díaz Angélica (BMC, 2011)
Abstract Background Pregnancy is accompanied by several hemodynamic, biochemical and hematological changes which revert to normal values after labor. The mean values of these parameters have been reported for developed countries, but not for Mexican women. Furthermore, labor constitutes a stress situation, in which these factors may be altered. It is known that serologic increase of heat shock protein (Hsp) 70 is associated with abnormal pregnancies, presenting very low level in normal pregnant women. Nevertheless, there are no studies where these measurements are compared in healthy pregnant women at their third trimester of pregnancy (3TP) and the active labor phase (ActLP). Methods Seventy five healthy Mexican pregnant women were included. Hemodynamic, biochemical and hematological parameters were obtained in all cases, and serum Hsp70 levels were measured in a sample of 15 women at 3TP and at ActLP. Results Significant differences were found in most analysis performed and in Hsp70 concentration at 3TP as compared to ActLP, however all were within normal range in both conditions, supporting that only in pathological pregnancies Hsp70 is drastically increased. Conclusion Results obtained indicate that 3TP and ActLP have clinical similarities in normal pregnancies, therefore if abnormalities are found during 3TP, precautions should be taken before ActLP.